Design, synthesis, and evaluation of phenylglycinols and phenyl amines as agonists of GPR88. Issue 7 (1st April 2015) - Dzierba, Carolyn D.; Bi, Yingzhi; Dasgupta, Bireshwar; Hartz, Richard A.; Ahuja, Vijay; Cianchetta, Giovanni; Kumi, Godwin; Dong, Li; Aleem, Saadat; Fink, Cynthia; Garcia, Yudith; Green, Michael; et al.
Graphical abstract: Abstract: Small molecule modulators of GPR88 activity (agonists, antagonists, or modulators) are of interest as potential agents for the treatment of a variety of psychiatric disorders including schizophrenia. A series of phenylglycinol and phenylamine analogs have been prepared and evaluated for their GPR88 agonist activity and pharmacokinetic (PK) properties.